Service Model Loyalty for School Yearbook Production at PT XYZ - Luni Aulia Safwani; Hartoyo; Suharjo, Budi (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Customer loyalty is a crucial aspect in the world of business and marketing, influencing sales, brand reputation, and company profits. The focus on customer loyalty is increasingly becoming a priority for many companies, including PT XYZ, a creative design company specializing in the production of School Yearbooks. Purpose: This research aims to identify the level of satisfaction and loyalty among PT XYZ customers, analyze the influence of marketing mix and service quality on customer satisfaction and loyalty, and formulate managerial implications for enhancing satisfaction and loyalty. Design/methodology/approach: The study involves 200 respondents purposively selected from 373 users of PT XYZ's services. Data collection was done through self-completion by respondents using an online questionnaire via Google Forms. Data analysis was conducted using modeling techniques that explain the relationship between loyalty, customer satisfaction, and the performance of the marketing mix and service quality. The estimation of model coefficients used the SEM-PLS rule. Descriptive analysis results indicate high satisfaction with the final product outcomes, while high loyalty is reflected in repeat purchases and recommendations to others. Findings/Result: The research findings show that all attributes of the marketing mix have a direct impact on customer satisfaction and loyalty. On the other hand, service quality has a direct impact on customer satisfaction but an indirect impact on loyalty, with customer satisfaction acting as a mediator. Conclusion: Managerial implications that can be formulated include improving marketing in Java Island, implementing marketing strategies through social media, maintaining consistency in product quality, enhancing service quality, implementing co-creating processes, and establishing a customer service division. These efforts are expected to address declining revenue and maintain customer loyalty for PT XYZ.Originality/value (state of the art): This study uniquely explores customer satisfaction and loyalty in the niche market of school yearbook production. It integrates the marketing mix and service quality, using SEM-PLS to analyze their impacts. The research fills a gap by providing actionable insights specifically for creative design businesses, offering practical strategies to enhance customer loyalty and business performance. Keywords: consumer loyalty, customer satisfaction, marketing mix, service quality, School Yearbooks